Kepadatan Populasi Aedes sp. Di Kelurahan Tambakreja Kota Cilacap Menggunakan Ovitrap Atraktan Air Rendaman Jerami - Karimah, An Nisa Akhlaqul; Martini, Martini; Udijono, Ari; Sutiningsih, Dwi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Abstract: Cilacap City is an endemic area of dengue fever and in 2020 Tambakreja Village was one of the contributors to high dengue cases with an IR of 150,4/100,000 population. Ovitrap filled with straw attractants can monitor well the density of Aedes sp. because it emits carbon dioxide (CO2) and a characteristic odor emanating from ammonia that is attractive to mosquitoes. The purpose of this study was to determine the population density of Aedes sp. by the ovitrap method of modification of straw soaking water attractants. Methods: Field experimental research using a descriptive approach. Samples of 20 housing units using purposive sampling techniques. Data were obtained from the calculation of eggs trapped in ovitrap and the identification of larvae. Result: The number of eggs obtained is 1458 eggs, with an index of 31.25% (medium category). Aedes aegypti larvae were found more with a percentage of 66.1% than Aedes albopictus larvae with a percentage of 33.9%. Conclusion: The population of Aedes aegypti is more found in ovitrap inside the house with a percentage of 94.3%, while Aedes albopictus in ovitrap outside the home with a percentage of 53.4%. The Health Office and local communities should immediately carry out control by eliminating potential breeding sites and controlling using larvicides.Keywords: Straw Soaking Water, Ovitrap, Aedes aegypti, Aedes albopictus, Cilacap